The logical intention of Genus in an understanding of transcendental concepts - Vyšniauskas, Gintautas (Verbum – Analecta Neolatina, 2004)
Predicating the universal properties of things to God we inevitably cast the net of logical intentions on Him. Only later can we disentangle Him from it by means of additional thinking. Therefore, it is probable that Aquinas says “Deus autem ponitur primum principium, non materiale, sed in genere causae efficientis” (S.T. I, 4, 1 in c.) just because here he looks at the infinite perfection of God through the limited perfection of things and wants to remind us that in such a perspective God is seen quasi in the genus. It is very important that Aquinas does not say, “Deus est in genere”, but: “Deus ponitur in genere” (emphasis mine). The neglecting of this diVerence between the est and the ponitur and interpreting the latter as if it were the former compels the translators form Latin to substitute genus by other terms. But these substitutions are doubtful.